A conceptual framework for effective learning engagement towards interface design of teaching aids within tertiary education - NORFADILAH KAMARUDDIN; SHAHRUNIZAM SULAIMAN (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This paper aims to draw attention to the value of pedagogical aids and to analyze how well they facilitate active learning at the tertiary level through the application of interface design principles.Methodology: In this paper, we conduct an exploratory literature review to determine whether interface design fundamentals’ principles and elements guidelines can be applied to improve learning engagement through clear and effective visual communication.Findings: This research delves into the fundamentals of how interactive teaching tools can foster meaning fullearning experiences for students and instructors.Implications/Novelty: The proposed model will further enhance the efficient engagement of Gen Y students by emphasizing the significance of understanding the principles and elements of multimedia interface design of the teaching aids. It is hoped that this research will point the way to additional studies to determine the principles and element guidelines for multimedia teaching aids toward an effective learning engagement for a wide range of educational levels of study.